Pengembangan Multimedia IPA Dengan Model Quantum Teaching Di SD Kecamatan Lakarsantri Surabaya - Zuni Eka Tiyas Rifayanti (Prodi PGSD FIP UNM, 2017)
The aims of this research are to develop science teaching media to determine the effectiveness and student learning outcomes in class V SD district Lakarsantri. Subjects in this study were students of SDN Jeruk II Surabaya. The stages of this research as follows: (1) analysis of learning, (2) define the general objectives of learning, (3) selecting methods, media and materials, (4) use of media, (5) students require participation, (6) evaluation and revision. Then the media science learning tested to the classroom VA with consist 23 students in SDN Jeruk II Surabaya and class VB 22 students in SDN Jeruk II Surabaya to know the results of student learning after learning activities using the model of Quantum Science Multimedia Teaching. Instrument used in this research activity includes: (1) questionnaire, (2) interview, (3) observation sheets, (4) test. The data will be analyzed using qualitative descriptive analysis, quantitative descriptive analysis and t test. Based on the hypothesis test between the experimental group and the control group by consulting t value and t table value, it can be concluded that Ho is rejected and Ha accepted because t value 2,450> 2,021 t tabel value. In other words, there is a comparison of Multimedia treatment IPA model Quantum Teaching Science learning outcomes on the results of the process of the water cycle and human activities that affect the class VA 23 students in SDN Jeruk II Surabaya and class VB 22 students in SDN Jeruk II Surabaya. Based on the research results can be concluded that: (1) Development of multimedia learning science with Quantum Teaching models can provide an alternative medium of learning in science subjects in class V. (2) There is the effect of the use of multimedia IPA model Quantum Teaching towards improving student learning outcomes in science lessons on the water cycle processes and human activities that affect the class VA 23 students in SDN Jeruk II Surabaya and class VB students in SDN Jeruk II Surabaya.Keywords: Multimedia Learning, Model of Quantum Teaching